Food Expenditure and Food Consumption before and during Ramadan in Moroccan Households - Imane Barakat (Hindawi Limited, 2020)
Fasting in the month of Ramadan is a religious, cultural, and social ritual for Muslims. The benefits it is supposed to provide to people who practice it are often impaired by unhealthy lifestyles including diet. The present research aimed to study risky eating behaviors and the variation in food expenditure of the Moroccan population during Ramadan. This study was conducted in 2018 in 340 households in urban and rural localities in the Rabat-Salé-Kenitra region of Morocco. Information on eating habits was collected by a nutritional survey using the method of dietary history; household food expenditure and sociodemographic characteristics were collected by a questionnaire. The average age of the population is 40 ± 14 years; the majority (40%) has a middle standard of living, and the average food expenditure increased by 50% during Ramadan. The food survey showed a significant increase in energy intake (p<0.001), carbohydrate intake (p<0.001), sucrose intake (p=0.02), sodium intake (p<0.001), and calcium intake (p<0.001) and a significant decrease in protein intake (p<0.001) and lipid intake (p<0.001), with no significant change in saturated fatty acid intake (p=0.86) during Ramadan. These results show that some dietary behaviors adopted during Ramadan could promote the development or worsening of overweight and chronic diseases. These data reveal the importance of nutritional education adapted to this sacred month.